The new Quest for Healing: when Therapy and Spirituality Intermingle - Ugeux, Bernard (International review of mission, 2007)
For some decades one has noted an increased interest in spirituality outside the traditional religions of the West, viz. the three monotheisms. New spiritual quests often develop on the fringes of the churches, and sometimes even as a reaction to the churches' vision of what it means to be human. In this regard, those interested in spirituality often see their spiritual search as something linked to a general care for wellbeing or health, and reproach Christianity for being too disembodied. The association of the spiritual with the therapeutical leads to a certain permeability between the spiritual and therapeutical in terms of the claims each makes. It also leads to the creation of new alternative proposals. This porousness runs the risk of bringing confusion to everything, and using the spiritual and religious to serve therapeutic needs. However, the way in which the claims of the spiritual and therapeutical realms evolve presents a challenge to Christianity. This can be put in terms of, ‘What place does Christianity attribute to the body, affectivity, pleasure, and legitimate personal development?’ Some individuals and groups in the Christian churches, rather than trying to justify existing approaches, propose more “incarnated” ones that will respond to the new audience in a Christian way. From a theological, pastoral and missiological viewpoint, Christian communities are thus intended to become communities of healing and reconciliation, although not at any price. If Christian spirituality also has to favour the empowering and development of a person — for Christ has assumed everything of humanity, except sin — one should not reduce salvation to healing or ignore the paschal mystery as a way of avoiding the element of pain that this mystery contains. In short, Christianity is invited to do a work of inculturation that not only keeps in mind contemporary developments but also is accompanied by an authentic interdisciplinary discernment.